Educação infantil e avaliação: implicações da política educacional na percepção dos docentes do município Lagoa de Dentro-PB - Silva, Déborah Kallyne Santos da (2020)
This study aimed to analyze the evaluation proposal for Early Childhood Education in Lagoa de Dentro-PB and the implications of the current educational policy in the perception of teachers. In the school practice of teachers of Early Childhood Education, several questions emerge regarding the evaluation, highlighting the need for dialogue with educational policies and a better understanding of the organization of pedagogical work. Thus, the problem with this research was the following: How is the assessment for Early Childhood Education carried out in the municipality and what are the implications of educational policies in the perception of their teachers? From a methodological point of view, it is a qualitative, documentary and exploratory research. We will use a dialectical perspective to support knowledge and analysis of concrete social and educational realities, as well as to understand the contradictions that are part of these realities. The research subjects were 12 teachers, from Pre I and II classes working in the city. In the field research, a questionnaire was applied. The data were analyzed starting from an organization, transcription and tabulation in dialogue with the categories that will be analyzed through critical hermeneutics. To theoretically subsidize this discussion, we have chosen the works of Afonso, Freitas, Hoffman, Saviani, Marsiglia, Arce, Hermida and Pasqualini as main theoretical contributions. The text ends with the presentation of the final considerations, among which we highlight the following: despite the public educational policies for early childhood education presenting proposals for the organization of pedagogical work at school, reality presents a hybrid educational practice (improvisation, pragmatism), indicating the need to strengthen the relationship between assessment in and Early Childhood Education so that the policy presents support from the concrete reality.